Tetracycline Effects on Candida Albicans Virulence Factors. (11th May 2008) - McCool, Logan; Mai, Hanh; Essmann, Michael; Larsen, Bryan
Abstract : Object . To determine if tetracycline, previously reported to increase the probability of developing symptomatic vaginal yeast infections, has a direct effect on Candida albicans growth or induction of virulent phenotypes. Method . In vitro, clinical isolates of yeast were cultivated with sublethal concentrations of tetracycline and yeast cell counts, hyphal formation, drug efflux pump activity, biofilm production, and hemolysin production were determined by previously reported methods. Results . Tetracycline concentrations above 150 μ g/mL inhibited Candida albicans, but at submicrogram/mL, a modest growth increase during the early hours of the growth curve was observed. Tetracycline did not inhibit hyphal formation at sublethal concentrations. Hypha formation appeared augmented by exposure to tetracycline in the presence of chemically defined medium and especially in the presence of human serum. Efflux pump CDR1 was upregulated and a nonsignificant trend toward increased biofilm formation was noted. Conclusion . Tetracycline appears to have a small growth enhancing effect and may influence virulence through augmentation of hypha formation, and a modest effect on drug efflux and biofilm formation, although tetracycline did not affect hemolysin. It is not clear if the magnitude of the effect is sufficient to attribute vaginitis following tetracycline treatment to direct action of tetracycline on yeast.